The Effect of Using KWL Strategy on Comprehending Descriptive Text at Tenth Grade Students of SMAN 3 Tapung Hulu - Heni Adetya Gultom; Novitri Syam; M Syarfi (Tell-us Journal)
The objective of this research is to find out whether there is significant effect of using KWL strategy on understanding descriptive text. This research is a quantitative research with pre-experimental research design (pre-experimental research method). The population of this research was the X grade students of SMAN 3 Tapung Hulu which amounted to 191 students. The sample was class X IPAS 2 which amounted to 30 students. This research data collection instrument uses multiple choice for pre-test and post-test. The results showed that the average post-test is 87.86 and the average pre-test is 68.53. From the results, it can be seen that there is a significant effect of using KWL strategy to comprehend descriptive text. Therefore, it can be concluded that the use of Know-Want to Know-Learned (KWL) strategy significantly improved the students' ability at SMAN 3 Tapung Hulu in understanding descriptive text.